Language learners' metasociolinguistic reflections: A window into developing sociolinguistic repertoires. (August 2018) - Beaulieu, Suzie; Woll, Nina; French, Leif Michael; Duchemin, Marie
Abstract: The present study sought to expand the growing line of research on the development of sociolinguistic competence in an instructed setting by examining the content of advanced French language learners' metasociolinguistic reflections after receiving explicit instruction on three frequent sociolinguistic features found in French. Three cohorts of students (N = 46) were enrolled in a 45-h advanced French second language course designed to introduce them to language variation phenomena found in (Canadian) French. At the end of each week, students were asked to produce metasociolinguistic reflections about how they intended to use the sociolinguistic variants targeted that week. Content analysis revealed that participants' reflections focused on two main aspects of their sociolinguistic development: (1) Noticing or assigning sociolinguistic value to linguistic resources, and (2) Perceived development of receptive and productive sociolinguistic knowledge. Based on the findings, suggestions to further support the development of sociolinguistic competence in a classroom setting are provided.